The Weaponization of Postmodernism: Russia's New War with Europe - P. B. Craik (London School of Economics and Political Science (LSE), European Institute, 2019)
The term 'information war' (IW) first came to public consciousness following the bizarre set of events surrounding Russia's 2014 annexation of Crimea. Since then, despite significant popular and academic interest in the topic, the nature of its deployment and the set of motivations behind it remain poorly understood. This paper seeks to address this. In it I argue that the Russian IW programme is best understood as an attempt to weaponize postmodernism. By this I intend not the aggressive advocacy of a set of intellectual postulates, but the promotion of a psychological weariness or scepticism that resembles what we might call the postmodern condition. Its aim, I argue, is to aid in the establishment of a multipolar international order, one that insulates the Putin regime against the spread of ideas disruptive to its rule at home.
Keywords: 330; Russia; Putin; European Union; information warfare; RT intergovernmentalism